Synthetic generation of streamflow data using computer simulation model - LEVAN K. V; Dr. Jobi V. Paul (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
Synthetic generation of streamflow data using computer simulation model
Synthetic generation of streamflow data using computer simulation model